Representasi Konflik Sosial dalam Novel Burung Kayu Karya Niduparas Erlang - Ginting, Alicia Agustina; Darma Putra, I Nyoman; Jumadiah, Sri (Stilistika : Journal of Indonesian Language and Literature; Vol 1 No 2 (2022): Volume 1 No. 2. April 2022, 2022)
As a homo conflicus creature, humans cannot avoid conflict. Conflict is a part of human life that inspire literary writer to write story. The novel Burung Kayu (Wood Bird, 2021) by Niduparas Erlang set in a region in Mentawai, North Sumatera, and expresses social conflicts that reflect the local situation. This article discusses three issues related to the novel, including (1) how is the structure of the novel Burung Kayu by Niduparas Erlang related to plot, characterization, and setting; (2) how is the representation of social conflict in Burung Kayu by Niduparas Erlang; (3) what is the meaning of the representation of social conflict in the novel Burung Kayu by Niduparas Erlang. The theory used is the theory of social conflict from the view of Lewis A. Coser, besides that, the theory of structure from the view of Stanton is used to examine the structure of the novel Burung Kayu . The data was collected using the literature study method with reading, listening, and note-taking techniques. Data analysis was carried out by interpretive descriptive method. Based on the analysis results of the novel Burung Kayu by Niduparas Erlang, it is built on conventional plots and flashbacks, the characterizations consist of main and complementary characters, then the setting is divided into place, time, atmosphere, and social. All of these elements are intertwined in the inter-element relationship and reflected social conflict of community where the story is set.